mRNA spindle localization and mitotic translational regulation by CPEB1 and CPEB4 - Pascual, Rosa (2021)
Transition through cell cycle phases requires temporal and spatial regulation of gene expression to ensure accurate chromosome duplication and segregation. This regulation involves dynamic reprogramming of gene expression at multiple transcriptional and posttranscriptional levels. In transcriptionally silent oocytes, the CPEB-family of RNA-binding proteins coordinates temporal and spatial translation regulation of stored maternal mRNAs to drive meiotic progression. CPEB1 mediates mRNA localization to the meiotic spindle, which is required to ensure proper chromosome segregation. Temporal translational regulation also takes place in mitosis, where a large repertoire of transcripts is activated or repressed in specific cell cycle phases. However, whether control of localized translation at the spindle is required for mitosis is unclear, as mitotic and acentriolar-meiotic spindles are functionally and structurally different. Furthermore, the large differences in scale-ratio between cell volume and spindle size in oocytes compared to somatic mitotic cells may generate distinct requirements for gene expression compartmentalization in meiosis and mitosis. Here we show that mitotic spindles contain CPE-localized mRNAs and translating ribosomes. Moreover, CPEB1 and CPEB4 localize in the spindles and they may function sequentially in promoting mitotic stage transitions and correct chromosome segregation. Thus, CPEB1 and CPEB4 bind to specific spindle-associated transcripts controlling the expression and/or localization of their encoded factors that, respectively, drive metaphase and anaphase/cytokinesis.